Cross-Species Transmission and Evolution of SIV Chimpanzee Progenitor Viruses Toward HIV-1 in Humanized Mice - Schmitt, Kimberly; Curlin, James; Remling-Mulder, Leila; Moriarty, Ryan; Goff, Kelly; O’Connor, Shelby; Stenglein, Mark; Marx, Preston; Akkina, Ramesh (Frontiers in Microbiology, 2020)
The genetic evolution of HIV-1 from its progenitor virus SIV following cross-species transmission is not well understood. Here we simulated the SIVcpz initial transmission to humans using humanized mice and followed the viral evolution during serial passages lasting more than a year. All three SIVcpz progenitor viruses used, namely LB715 and MB897 (group M) as well as EK505 (group N) readily infected hu-mice resulting in chronic viremia. Viral loads increased progressively to higher set-points and the CD4+ T cell decline became more pronounced by the end of the second serial passage indicating viral adaptation and increased pathogenicity. Viral genomes sequenced at different time points revealed many nonsynonymous variants not previously reported that occurred throughout the viral genome, including the gag, pol, env and nef genes. These results shed light on the potential changes that the SIVcpz genome had undergone during the initial stages of human infection and subsequent spread.